2016
DOI: 10.4137/cmped.s38338
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of the Enteric Microbiome on the Development of Childhood Disease: A Review of Prebiotic and Probiotic Therapies in Disorders of Childhood

Abstract: Recent studies have highlighted the fact that the enteric microbiome, the trillions of microbes that inhabit the human digestive tract, has a significant effect on health and disease. Methods for manipulating the enteric microbiome, particularly through probiotics and microbial ecosystem transplantation, have undergone some study in clinical trials. We review some of the evidence for microbiome alteration in relation to childhood disease and discuss the clinical trials that have examined the manipulation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 328 publications
(437 reference statements)
0
44
0
1
Order By: Relevance
“…Deficiencies in these enteric bacteria could be linked to ASD through environmental factors. Of note, Bifidobacteria is primarily obtained through breastfeeding and reduced breastfeeding has been linked to ASD, and western diets, which have been linked to ASD, are low in Prevotella [18]. A recent small open-label clinical trial showed that microbiota transfer therapy significantly improved gastrointestinal and ASD symptoms in children and adolescents with ASD [16].…”
Section: The Importance Of the Microbiome And Folate Transporters In Fomentioning
confidence: 99%
See 1 more Smart Citation
“…Deficiencies in these enteric bacteria could be linked to ASD through environmental factors. Of note, Bifidobacteria is primarily obtained through breastfeeding and reduced breastfeeding has been linked to ASD, and western diets, which have been linked to ASD, are low in Prevotella [18]. A recent small open-label clinical trial showed that microbiota transfer therapy significantly improved gastrointestinal and ASD symptoms in children and adolescents with ASD [16].…”
Section: The Importance Of the Microbiome And Folate Transporters In Fomentioning
confidence: 99%
“…Folate is synthesized by enteric bacterial species, particularly Bifidobacteria, Prevotella and certain Lactobacilli species [13][14][15][16][17]. Children with ASD lack microbial diversity and have a decreased abundance in both Prevotella and Bifidobacteria, potentially leading to reduced folate production by microbiota in individuals with ASD [18]. Deficiencies in these enteric bacteria could be linked to ASD through environmental factors.…”
Section: The Importance Of the Microbiome And Folate Transporters In Fomentioning
confidence: 99%
“…These bacteria include Clostridia and other species producing propionic acid and related fatty acids by antibiotic-resistant gut bacteria that can increase the risk of autism or worsen its symptoms. They tend to overgrow in the gut following a course of antibiotics that wipes out other intestinal bacteria causing intestinal inflammation 11,12 .…”
Section: Microbiomementioning
confidence: 99%
“…In contrast, probiotics are microorganisms that are administered to directly colonize an organ system. The number of microbes living in the gastrointestinal (GI) tract is ten times the number of human cells in the body, and the total microbial genetic material is 100 times that of the entire human genome (2). In fact, the gut micro-biome has been referred to as the “second genome” of the human body.…”
mentioning
confidence: 99%